Relationship between the CUBN and the MIA3 gene copy number variation and growth traits in different cattle breeds - Yue Han; Jiwei Liu; Congcong Zhang; Ming Sun; Xuanyu Li; Hongliang Liu; Shengnan Li; Yongchao Zhu; Ruidong Li; Xiaotong Luo; Yumin Zhao; Jian Wu (Animal Biotechnology)
Copy number variations (CNV) are important genetic variations. The endogenous factors cobalamin receptor (CUBN) and MIA SH3 domain ER-derived factor 3 (MIA3) are associated with bone/muscle development and intramuscular fat deposition. There have been no reports on the effects of CUBN and MIA3 CNVs on growth traits of Chinese cattle. This study aimed to determine the correlation between the CUBN and MIA3 CNVs and growth traits in Chinese cattle. qRT-PCR was used to detect the distribution of CUBN and MIA3 CNV and the expression levels of their mRNA, and correlation analysis was conducted between CNV and growth traits. The CUBN was differentially expressed in different breeds of cattle, and CUBN CNV correlated significantly with body height, hip height, body slanting length, and hip width of Grassland Red cattle (CYH); eye muscle area of Yanbian cattle (YB) and Yan Yellow cattle (YH). MIA3 showed no CNV in CYH and YB cattle, and only one deletion type occurred in YH cattle. CUBN and MIA3 mRNA have different expression patterns in different cattle breeds and tissues. In conclusion, CUBN CNV is correlated significantly with growth traits in Chinese cattle and is a novel molecular marker that could be exploited in cattle breeding.